Mapping of lamtoro field in supporting the co-firing of steam power plants program - Yasin Mohamad; Sardi Salim; Lanto Mohamad Kamil Amali; Abdi Gunawan Djafar (Institute of Advanced Engineering and Science, 2023)
The policy of renewable energy in Indonesia is expressed in the government regulation no. 79 in 2014 regarding the national energy policy. In the document, renewable energy is targeted to reach 23% in 2025, and a minimum of 31% in 2050. One of the developed renewable energies is biomass which is produced by lamtoro, a plant which has been employed as a mixture in coal at Anggrek steam power plant 2×25 MW Gorontalo. As much of 1% to 5% of lamtoro is added in 1,000 ton of coal per day. The research aims to create a thematic map of the distribution of lamtoro to meet the need of co-firing at Anggrek steam power plant. The result of research shows the total area of field which has been planted with lamtoro is 69,074 ha, scattered in 14 districts. Meanwhile the largest area is Kabila Bone district (22,070 ha), and the smallest area is East Bulango district (0.228 ha). The estimated potential of lamtoro in 14 districts of Bone Bolango regency is about 916,439.86 ton/ha/year.